2017
DOI: 10.1177/0734242x16686412
|View full text |Cite
|
Sign up to set email alerts
|

A novel risk assessment method for landfill slope failure: Case study application for Bhalswa Dumpsite, India

Abstract: Rapid population growth of major urban centres in many developing countries has created massive landfills with extraordinary heights and steep side-slopes, which are frequently surrounded by illegal low-income residential settlements developed too close to landfills. These extraordinary landfills are facing high risks of catastrophic failure with potentially large numbers of fatalities. This study presents a novel method for risk assessment of landfill slope failure, using probabilistic analysis of potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
0
9
0
2
Order By: Relevance
“…It should be noted that the factor of safety distribution only determines the P f , but the failure surfaces on the landfill slope can be very different from each other and the volume of displaced waste in them may have very different values. As a result, combining the results of the P f and failure area calculation can lead to a better determination of the risks of landfill failure (Jahanfar et al, 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the factor of safety distribution only determines the P f , but the failure surfaces on the landfill slope can be very different from each other and the volume of displaced waste in them may have very different values. As a result, combining the results of the P f and failure area calculation can lead to a better determination of the risks of landfill failure (Jahanfar et al, 2017b).…”
Section: Resultsmentioning
confidence: 99%
“…A slope will fail only if the FOS is lower than unity, which is the probability of failure (P(FOS < 1)). Table 6 shows the mean and coefficient of variation (COV) of the required data for MSW cohesion and friction angle probabilistic distributions, which were derived from values in the literature [4,19] and technical code for geotechnical engineering of municipal solid MSW sanitary landfills [31]. Previous research has shown that the friction angle and cohesion of the MSW follow normal and log-normal distributions, respectively [18,19].…”
Section: Quantitative Risk Assessment Of Potential Landfill Failurementioning
confidence: 99%
“…Landfills are the dominant MSW disposal method in China, which are prone to fail in the rainy season. Failure results in severe pollution to the environment and threaten the lives and properties of people in the surrounding area once the failure occurs [3,4]. Landfill failures have frequently occurred all over the world in recent years (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…During this stage the largest number of failures is most probable to occur, including: In case of any of these failures, there is a serious threat of surface and groundwater pollution, caused by the leachate infiltrating the subsoil. Landfill leachate is a complex mixture characterized by high toxicity, able to contaminate soils and waters surrounding the landfill [17,18] or penetrate deeper soil layers reaching drinking water source zones [14,15,19]. Once the leachate releases into the soil, it will interact physically and chemically with both the adjacent groundwater and the soil matrix [20].…”
Section: Failures Of Landfill Structural Elements As Hazards Posed Onmentioning
confidence: 99%